Konstruksi Kepercayaan Diri Anak Usia 4-5 Tahun Melalui Intervensi Pedagogis Guru - Cepi Ramdani; Iis Basyiroh; Dede Hikmah; Monalisa Monalisa (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
This study aims to examine the construction of self-confidence in children aged 4–5 years through teacher pedagogical interventions in school learning. This study used a qualitative approach with a descriptive design. Data collection techniques included observation, interviews, and documentation. The results showed that children's self-confidence was constructed through pedagogical interactions integrated into the learning process. Teachers acted as facilitators, motivators, and models in creating a supportive and psychologically safe learning environment. In addition, successful experiences through demonstration activities and the use of the environment as a learning resource also strengthened children's self-confidence. This finding confirms that the development of children's self-confidence is multidimensional and has an impact on community development. The implications of this research emphasize the importance of pedagogical competence and social-emotional sensitivity of teachers in child-centered learning.